2017
DOI: 10.1038/s41598-017-10309-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of invariant natural killer T cells stimulated with microbial α-mannosyl glycolipids

Abstract: Some synthetic and bacterial glycolipids presented by CD1d specifically activate invariant NKT (iNKT) cells bearing an invariant Vα14-Jα18 (mouse) or Vα24-Jα18 (human) TCR. The antigenic glycolipids identified to date consist of two hydrophobic chains and an α-glycoside in which the 2′-OH group is in the cis orientation toward the anomeric group, namely, either an α-galactoside or an α-glucoside. Several microbial α-mannosyl glycolipids, in which the 2′-OH group is in the trans orientation, were herein examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…35,36 NKT cells recognize glycolipid antigens, such as glycosylceramides, present in the cell wall of Gram-negative bacteria. [37][38][39] NKT cells can recognize lipid antigens and thus broaden the repertoire of antigens recognized by conventional T cells. In addition, in spite of the limited diversity of T-cell receptors (TCR) in NKT cells, they recognize many different microorganism antigens, which points to the high plasticity of their TCRs.…”
Section: Nkt Cells (%)mentioning
confidence: 99%
“…35,36 NKT cells recognize glycolipid antigens, such as glycosylceramides, present in the cell wall of Gram-negative bacteria. [37][38][39] NKT cells can recognize lipid antigens and thus broaden the repertoire of antigens recognized by conventional T cells. In addition, in spite of the limited diversity of T-cell receptors (TCR) in NKT cells, they recognize many different microorganism antigens, which points to the high plasticity of their TCRs.…”
Section: Nkt Cells (%)mentioning
confidence: 99%
“…Interestingly, similar to A. fumigatus, Histoplasma capsulatum and Alternaria alternata, C. albicans activates iNKT cells via fungal β1,3-glucan recognition by Dectin-1 and subsequent IL-12 secretion by activated CD1d-expressing antigen-presenting cells in vitro [135]. In another study, it was shown that cholesteryl 6 -O-acyl α-mannoside, found in C. albicans induced activation of mouse and human iNKT cells, dependent on CD1d [136]. However, intravenous C. albicans infection of J alpha 18KO mice which specifically lack iNKT cells, has shown that iNKT cells play a minor role in controlling systemic C. albicans infections since survival, fungal burden, and production of inflammatory cytokines in several organs did not significantly change during infection [137].…”
Section: Inktmentioning
confidence: 96%
“…Mechanistically, this protective activity relied on IFN-γ and IL-17A production and subsequent neutrophil recruitment that controlled bacterial elimination ( 164 ). While these protective effects have been obtained using α-GalCer, exogenous activation of type I NKT cells with α-mannosylglycolipids has also been shown to partially protect mice against pneumococcal infection ( 165 ).…”
Section: Cd1d-restricted Nkt Cells and Mr1-restricted Mait Cells In Lmentioning
confidence: 99%